A coded aperture-based 3D SPECT imaging system for early breast cancer detection - Hussain, Khalid (2023)
Single Photon Emission Computed Tomography (SPECT) is an established imaging modality that is undertaken using a parallel-hole collimator. This technique suffers from clinical limitations as it has less reliability in detecting small lesions (less than one centimeter in diameter) due to trade-off between sensitivity and resolution. Instead of a collimator, this study proposes a coded aperture (CA) based SPECT imaging system where a mask is attached to a typical clinical gamma camera. This imaging method investigates different patterns of the Modified Uniformly Redundant Array (MURA) masks and mosaic MURA masks by a simulating point source, planar source, and the 3D realistic anthropomorphic female breast phantom. For the breast phantom, simulations were repeated for different lesion sizes and the tumor-to-background ratio (TBR). The proposed CA-based SPECT camera employs a mosaic MURA mask and antimask combined with the Maximum Likelihood Expectation Maximization (MLEM) algorithm. The antimask reconstructed images are subtracted from the mask images to suppress the background noise and minimize the non-uniformity in the background slice by slice. The reconstructed slices are stacked to give a 3D image. Mosaic MURA mask antimask subtraction has improved the quality of reconstructed images, allowing visualization of 3 mm diameter breast lesions using 10:1 TBR. The purpose of this research is to prove the feasibility of 3D reconstruction, and the aforementioned background could be shielded either through proper physical shielding and/or through the particular detection angle of a gamma camera. Ultimately, this study has proved that 3D reconstruction of the breast phantom is possible using CA-based SPECT imaging. Moreover, 3D reconstruction can be achieved from a single projection instead of a sinogram. This study has successfully detected a lesion of 3 mm diameter with TBR 10:1. The chest, heart, and lung background radiation effects are not included in this study and can be investigated in future.